2008
DOI: 10.1002/pssb.200844062
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interface trap parameters from double‐peak conductance spectra taken on N‐implanted 3C‐SiC MOS capacitors

Abstract: 3C‐SiC/SiO2 capacitors are fabricated by over‐oxidation of an implanted Gaussian nitrogen (N) profile and investigated by conductance spectroscopy. An unexpected double peak structure is observed in the conductance spectra indicating two types of independent traps at different energy positions in the bandgap, which change their charge state with identical time constant. A theoretical model is developed assuming two independent distributions of interface traps in the bandgap of 3C‐SiC with different trap parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Also, all of the G-V curves have finite FWHM, suggesting that these traps are distributed over an energy range within the bandgap and are not localized at a fixed energy value. Similar results have been reported for nitrogen-implanted 3C-MOS-C. 20 Also, lateral MOSFET were fabricated by use of different oxidation temperatures. The results of mobility measurements for lateral MOSFET are shown in Table I, values of measured field-effect mobility (l) are compared with data previously reported for 3C-SiC MOSFET.…”
Section: Methodssupporting
confidence: 57%
“…Also, all of the G-V curves have finite FWHM, suggesting that these traps are distributed over an energy range within the bandgap and are not localized at a fixed energy value. Similar results have been reported for nitrogen-implanted 3C-MOS-C. 20 Also, lateral MOSFET were fabricated by use of different oxidation temperatures. The results of mobility measurements for lateral MOSFET are shown in Table I, values of measured field-effect mobility (l) are compared with data previously reported for 3C-SiC MOSFET.…”
Section: Methodssupporting
confidence: 57%
“…By comparing the voltage position of the conductance peaks in the C-V curves, it implies that one of the peaks appears at higher voltage than the flatband voltage, while the other one appears at lower voltage. Then according to the voltage position at which the hump occurs, below the flatband voltage, we can deduce that one of the conductance peaks is due to standard ITs, whereas the other one is due to NIOTs ͑as already reported by Krieger et al 33 ͒. Referring to the bench-marking ͑process 1͒, the anomalous hump and thereby the double conductance peak are even more pronounced for N 2 incorporation during the process steps ͑pro-cesses 2-4͒, showing an enhancement of the NIOT density.…”
Section: G17mentioning
confidence: 81%
“…2͑b͔͒. Recently, Krieger et al 6 has also reported double-peak conductance spectra for 3C-SiC MOS capacitors fabricated using nitrogen implantation followed by oxidation in pure oxygen. The proposed model 6 attributes two conductance peaks to the presence of two different kinds of interface traps: carbon clusters at the interface ͑energeti-cally shallow states͒ and carbon clusters bound with nitrogen interface donor ͑energetically deep states͒.…”
Section: A 3c-sic Materialsmentioning
confidence: 95%